INDONESIA CAPITAL MARKET REACTION TO GREEN INVESTING IMPLEMENTATION - Putri, Febrian Eka; Halimatusyadiah, Halimatusyadiah (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
This study aims to see the differences and investor responses to the implementation of green investing in the Indonesian Capital Market, will investors prefer to invest in companies that implement environmentally friendly operations. Are there differences and investor responses before and after the implementation of green investing with the launch of an ESG (Environmental, Social, and Governance)-based index, the index is ESG Quality 45 IDX Kehati Index on December 20, 2021. The research sample comprises all companies included in the ESG Quality 45 IDX Kehati Index , i.e. 45 companies with a large, liquid market capitalization, that have an ESG score above the minimum threshold and the Company's operations are based on ESG (Environmental, Social, and Governance) or environmentally friendly. The data collection technique is the documentation method to obtain data on stock prices, trading volume activity, and IHSG. The data processing methods used are descriptive analysis and difference tests. With a significance value of 0.001, the data demonstrate that the average share or stock price changed significantly before and after the Index was included. The significance value of the paired sample t-test before and after the company entered the index showed values of 0.0640 and 0.179, indicating that there was no significant difference between the abnormal return and trading volume activity of the company before and after entering the index. In addition, investors did not react significantly to the Company included in the ESG Quality 45 IDX Kehati Index.